ChemInform Abstract: Solvent‐Free Chemoselective Oxidation of Thioethers and Thiophenes by Mechanical Milling. Issue 14 (20th March 2013) - Cravotto, Giancarlo; Garella, Davide; Carnaroglio, Diego; Gaudino, Emanuela Calcio; Rosati, Ornelio
Abstract A green procedure for the selective oxidation of several organosulfur compounds to the corresponding sulfones using Oxone is developed.